Configuration and Experimental Implementation of Three-Phase Brushless Linear Motor - Mohd Sufian bin Ishak, Mohd Sufian (Universiti Teknologi Petronas, 2011)

(untitled)
A linear motor is an electromechanical device where an electrical input determines the position of the translator – the moving part of the linear motor. The purpose of this project entitled “Configuration and Experimental Implementation of Three Phase Brushless Linear Motor” is to configure both hardware and software in setting up a linear motor testing facility. Hardware configuration is mainly on the linear motor, motor driver from Copley Controls and a PC-based controller. The software used for configuration and operation of the linear motor and controller also from Copley Controls. After all configurations are completed, a three phase current transducer will be installed in series between the linear motor and the motor driver. The purpose of the current transducer is to capture waveforms of the input current from the motor driver to the linear motor. There are three phases of input currents and these current waveforms will be measured for analyses on linear motor commutation and switching strategies.